Targeting ApoC3 Paradoxically Aggravates Atherosclerosis in Hamsters With Severe Refractory Hypercholesterolemia - Xu, Yitong; Guo, Jiabao; Zhang, Ling; Miao, Guolin; Lai, Pingping; Zhang, Wenxi; Liu, Lili; Hou, Xinlin; Wang, Yuhui; Huang, Wei; Liu, George; Gao, Mingming; et al. (Frontiers in Cardiovascular Medicine, 2022)
Rationale ApoC3 plays a central role in the hydrolysis process of triglyceride (TG)-rich lipoproteins mediated by lipoprotein lipase (LPL), which levels are positively associated with the incidence of cardiovascular disease (CVD). Although targeting ApoC3 by antisense oligonucleotide (ASO), Volanesorsen markedly reduces plasma TG level and increase high-density lipoprotein cholesterol (HDL-C) in patients with hypertriglyceridemia (HTG), the cholesterol-lowering effect of ApoC3 inhibition and then the consequential outcome of atherosclerotic cardiovascular disease (ASCVD) have not been reported in patients of familial hypercholesterolemia (FH) with severe refractory hypercholesterolemia yet. Objective To investigate the precise effects of depleting ApoC3 on refractory hypercholesterolemia and atherosclerosis, we crossed ApoC3-deficient hamsters with a background of LDLR deficiency to generate a double knockout (DKO) hamster model (LDLR−/−, XApoC3−/−, DKO). Approach and Results On the standard laboratory diet, DKO hamsters had reduced levels of plasma TG and total cholesterol (TC) relative to LDLR−/− hamsters. However, upon high-cholesterol/high-fat (HCHF) diet feeding for 12 weeks, ApoC3 deficiency reduced TG level only in female animals without affecting refractory cholesterol in the circulation, whereas apolipoprotein A1 (ApoA1) levels were significantly increased in DKO hamsters with both genders. Unexpectedly, loss of ApoC3 paradoxically accelerated diet-induced atherosclerotic development in female and male LDLR−/− hamsters but ameliorated fatty liver in female animals. Further analysis of blood biological parameters revealed that lacking ApoC3 resulted in abnormal platelet (PLT) indices, which could potentially contribute to atherosclerosis in LDLR−/− hamsters. Conclusions In this study, our novel findings provide new insight into the application of ApoC3 inhibition for severe refractory hypercholesterolemia and ASCVD.